عصمة الأنبياء عند الأشاعرة في ضوء القرآن الكريم: نقد وتأصيل - راجح عبد الحميد سعيد (International Institute of Islamic Thought, 2015)
هذه دراسة نقدية أصولية في عصمة الأنبياء عند علماء الأشاعرة من أهل السنة في ضوء القرآن الكريم. فقد شكّلت هذه القضية مشكلة للبحث عند هؤلاء العلماء، من خلال تفسير ما ورد في قصص الأنبياء، مما له علاقة بالألفاظ والعبارات التي قد توهم في نظرهم التعارض مع العصمة، و قدّموا فهماً وتأويلاً حافظوا به على العصمة في نظرهم، كما نقلوا الإسرائيليات واضطروا لبحثها. وكان لهم فهم في تفسير آيات العصمة، مارسوا فيه منطق الدفاع بالرد على المخالفين في العصمة، وولَّد هذا الفهم إشكالات عند اعتماد المرجعية القرآنية. وقد حاول الباحث استنباط قواعد من القرآن الكريم في عرضه لقصص الأنبياء. وانتهى البحث إلى ضرورة بحث عصمة الأنبياء مع الالتزام بقواعد القرآن الكريم في فهمها. This study provides a critique and a foundation building of the infallibility of the Prophets as perceived by the Sunni Ash'arite scholars. The study takes the Qur'an as the basis for addressing this issue. For the Ash'arites, this theme has presented a problem in their effort to interpret the Qur'anic narrative about the Prophets, especially those narratives that present statements and expressions that may cause a conflict with infallibility. Since the Ash'arites have included stories from the Israelite sources, they found themselves compelled to discuss these stories. This understanding has yielded problems in interpretation when the Qur'anic authority is considered. The researcher attempts to identify Qur'anic principles in explaining the stories of the Prophets, and concludes with the need to re-address the issue of the Prophets' infallibility with a commitment to the Qur'anic principles.